Pengaruh Latihan Daya Ledak Otot Tungkai Terhadap Kemampuan Servis Sekrup Dalam Permainan Sepak Takraw Pada Siswa SMA Negeri 2 Tondano - Andycha Yunus; Doortje. F. Tamunu; Nofrie. J. Sondak (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The results of parametric statistical analysis focused on increasing the explosive power of leg muscles have a significant effect on the ability to perform screw serves in sepak takraw games in students of SMA Negeri 2 Tondano. This is evidenced by the difference in average values ​​based on the control group and the experimental group, where the experimental group experienced an increase of 4.30, while the control group was only 1.60. The results of the independent t-test showed that the calculated t value of 5.175 was greater than the t table of 2.101 at a significance level of 0.05, which means that there was a very different difference making it significant between the two groups. This study used a pre-test and post-test design with random group division, and data collection was carried out through a service ability test. The research sample consisted of 20 male students of SMA Negeri 2 Tondano, which was the entire population, then divided into two groups, namely the experimental group and the control group, each consisting of 10 people. The method used was an experimental method to directly test the impact of leg muscle explosive power training on improving screw serve skills. This study aims to determine how much influence the training has on the ability of service techniques, with the hypothesis that there is a positive influence of leg muscle explosive power training on screw service skills. The formulation of the problem that is the focus of this study is whether leg muscle explosive power training has an effect on increasing screw service skills in sepak takraw games in students of SMA Negeri 2 Tondano.